2015
DOI: 10.14436/2178-3713.5.1.030-039.oar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apical marginal leakage in teeth retrofilled with MTA-water and MTA-Fillapex: a study in avulsed teeth

Abstract: Introduction: Since periapical surgical therapy success depends on adequate apical seal, MTA has been recommended as the best retrofilling material.Objective: To assess whether the association between MTA and Fillapex sealer negatively affects the material apical sealing ability. To this end, apical leakage was tested with 1% rhodamine B was used. Methods: Fifty roots with straight canals were prepared by means of the ProTaper Universal system up to F5 instrument, and filled by means of the modified McSpaden t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…There are several studies in modern literature on micro leakage of MTA Fillapex. Antonio Braitt et al (4) found marginal leakage of MTA Fillapex of 0.34 mm. Relatively more is discovered by the team of Sönmez -between 3.1 and 10 mm [22].…”
Section: Discussionmentioning
confidence: 98%
“…There are several studies in modern literature on micro leakage of MTA Fillapex. Antonio Braitt et al (4) found marginal leakage of MTA Fillapex of 0.34 mm. Relatively more is discovered by the team of Sönmez -between 3.1 and 10 mm [22].…”
Section: Discussionmentioning
confidence: 98%